2023
DOI: 10.3390/ani13111742
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of Ultrasonography in the Evaluation of Mammary Tumors in Bitches

Abstract: The high incidence of mammary tumors in small animals is concerning. Patient history, clinical examination, physical evaluation, and imaging studies are important for clinical staging. Ultrasonography is commonly applied to investigate the presence of abdominal metastasis. However, it has been shown to provide important information regarding mammary tumors’ architecture and advanced sonographic techniques can provide information regarding neovascularization, stiffness, and perfusion. Different techniques have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Canine mammary gland tumour (MGT) is the most commonly diagnosed neoplasm, comprising the major proportion of reproductive tumours in female dogs ( Kuppusamy et al 2019 ). In addition, many retrospective studies have found that MGT has a high malignancy rate (approximately 50%) and a high metastatic potential (almost 50%)., mainly giving rise to mortality in dogs ( Im et al 2014 ; Feliciano et al 2023 ). Therefore, the early diagnosis and surgical resection are imperative, which allow the prevention of tumour progression and better prognosis.…”
mentioning
confidence: 99%
“…Canine mammary gland tumour (MGT) is the most commonly diagnosed neoplasm, comprising the major proportion of reproductive tumours in female dogs ( Kuppusamy et al 2019 ). In addition, many retrospective studies have found that MGT has a high malignancy rate (approximately 50%) and a high metastatic potential (almost 50%)., mainly giving rise to mortality in dogs ( Im et al 2014 ; Feliciano et al 2023 ). Therefore, the early diagnosis and surgical resection are imperative, which allow the prevention of tumour progression and better prognosis.…”
mentioning
confidence: 99%